Examining the impact of probiotic Lactiplantibacillus pentosus 6MMI on inhibiting biofilm formation, adhesion, and virulence gene expression in Listeria monocytogenes ATCC 19115 - Behrooz Alizadeh Behbahani; Mostafa Rahmati-Joneidabad; Morteza Taki (Biofilm)
Probiotic bacteria improve human health by secreting pro-microbial substances, balancing intestinal flora, binding to the mucous membrane and epithelium, strengthening the intestinal epithelial barrier, and creating interactions between the gastrointestinal microbiota and the immune system. This study aimed to investigate the probiotic potential, biofilm-related gene expression and anti-biofilm capabilities of Lactiplantibacillus pentosus 6MMI. The strain exhibited remarkable resilience to challenging conditions, including acidic environments, gastrointestinal settings, and bile salts. Notably, Lpb. pentosus demonstrated significant hydrophobicity (71.89 %), auto-aggregation (42.39 %), co-aggregation (51.28 %), antioxidant activity (ranging from 42.29 % to 64.61 %), and a cholesterol reduction capacity of 50.31 %. Its competitive abilities against Listeria monocytogenes were quantified, showing a competition rate of 54.51 %, displacement rate of 48.57 %, and inhibition of adhesion at 27.71 %. Also, Lpb. pentosus resulted an adhesion rate of 12.91 % to epithelial cells and showed no DNase or hemolytic activity. The strain exhibited the highest resistance to nalidixic acid, with an inhibition zone measuring 15.20 mm, while it was least resistant to chloramphenicol, which had an inhibition zone of 27.30 mm. Treatment with cell-free supernatant (CFS) from Lpb. pentosus significantly reduced biofilm formation by 91.25 % and 24.50 % and diminished mature biofilm formation by 83.82 % and 21.80 % on L. monocytogenes. Additionally, the CFS inhibited the transcription of the plcB, hly, and prfA genes in L. monocytogenes, suggesting a potential reduction in bacterial virulence through decreased hemolysin release and modulation of phospholipase activity. In the next step of the study, the Gaussian Process Regression (GPR) model accurately predicted bile tolerance and acid parameters with a high R2 of 0.99 and minimal Mean Absolute Percentage Error (MAPE) values of 0.33 % and 0.21 %, respectively. The residual errors showed a normal distribution, indicating reliable and consistent predictions. Overall, Lpb. pentosus 6MMI represents a valuable candidate for further investigation in probiotic development and biofilm management strategies.